Sustainability Disclosure in Annual Reports and Websites: A Study of the Banking Industry in Bangladesh - Farid Ahammad, Sobhani; Azlan, Amran; Yuserrie, Zainuddin (Elsevier Ltd., 2012)
This study aims to describe the status of disclosure practices of corporate sustainability in the annual reports and corporate websites of the banking industry in Bangladesh. It is revealed in the study that, to varying degrees, all listed banks practice sustainability disclosure in an unstructured manner in both the annual reports and corporate websites. The annual report surpasses the corporate website in the disclosure of all categories of corporate sustainability disclosure (CSD) practices except product responsibility disclosure. Unlike the environmental and economic dimensions, issues concerning the social dimension are generally disclosed. Islamic banks disclose more sustainability information in comparison to conventional banks. It is also found that among the three generation, the older bank does not outperform the younger bank in terms of the sustainability disclosure.